The comparison between curcumin and propolis against sepsis-induced oxidative stress, inflammation, and apoptosis in kidney of adult male rat - Areeg Abd-Elrazek; Sahar Mahmoud; Ahmed Abd ElMoneim (SpringerOpen, 2020)
Abstract Background Propolis is a honeybee product displaying an anti-inflammatory, antimicrobial, and antioxidant effect on several tested animal models. Curcumin a polyphenol extracted from turmeric that gained interest as a potentially safe and inexpensive treatment for kidney diseases. The present study aimed to compare the protective effects of curcumin and propolis on endotoxemia-induced renal dysfunction. Results Sepsis induction caused a marked decline in renal GSH, GPx, and GR, as well as antioxidant enzyme activities; CAT and SOD. Elevation in LPO, NO, IL-1β, and PGE2 contents were observed as well. A marked induction in Bax contents, Bax\Bcl2 ratio, accompanied by activation of NF-kB in the kidney of sepsis-induced rats was reported. However, Prop pretreatment of endotoxemic rats was effective in controlling the depletion of renal GSH content and its correlated enzymes; Cur was more potent in maintaining the renal CAT and SOD contents, as well as, dimensioning LPO content. Despite the renal inflammatory marker IL-1β, PGE2, NO contents, Bax\Bcl2 ratio, and NF-kB activation were greatly reduced by both curcumin and propolis, only Cur pretreatment attenuated NF-kB activation in kidney tissue of septic rat. Conclusion Though pretreatment of either Cur or Prop to septic rats protected their kidneys against oxidation, inflammation, and apoptosis status, Cur pretreatment was superior in protecting rats' kidney after sepsis induction.